Drynaria fortunei Promoted Angiogenesis Associated With Modified MMP-2/TIMP-2 Balance and Activation of VEGF Ligand/Receptors Expression - Huang, Sheng-Teng; Chang, Cheng-Chieh; Pang, Jong-Hwei S.; Huang, Hung-Sen; Chou, Shen-Chieh; Kao, Ming-Ching; You, Huey-Ling (Frontiers in Pharmacology, 2018)
Background and Purpose: Drynaria fortunei J. Sm (D. fortunei), known as Gu-Sui-Bu, is used in traditional Chinese medicine to treat common injuries, including bone fractures and bruising. However, the specific functional mechanisms of the angiogenic and endothelial cell migration properties of D. fortunei are currently unclear and require further elucidation. Experimental approach: The present study investigates, both in vivo and in vitro, the wound healing effects of D. fortunei as associated with angiogenesis, specifically by the modulation of matrix metalloproteinases (MMPs) and upregulation of vascular endothelial growth factor (VEGF) ligand/receptors. In order to determine the potential angiogenic effects of D. fortunei, in vivo neovascularization of chick chorioallantoic membranes (CAM) assay, and directed in vivo angiogenesis assay (DIVVA) were performed; while in vitro scratch wound healing, migration, and matrix-induced tube formation assays were performed by using human umbilical vascular endothelial cells (HUVECs). Furthermore, we used qPCR to analyze the gene expressions and Western blot to observe protein expressions of MMP-2, MMP-14, TIMP-2, RECK and VEGF/VEGFRs. Results: This study identified five major compounds from the water extract of D. fortunei: protocatechuic acid, caffeic acid 4-O-β-D-glucopyranoside, 5, 7-dihydroxychromone-7-O-rutinoside, neoeriocitrin, and naringin. D. fortunei was confirmed to activate in vivo angiogenesis by CAM and DIVVA assays. D. fortunei further exhibited in vitro angiogenic effects associated with cell migration, as demonstrated by the tube formation assay, transwell migration assay, and scratch wound healing assay. The extracellular MMP-2 activity was found to be dose-dependently augmented both in vitro and in vivo by D. fortunei. The mRNA and protein expressions of MMP-2, and MMP-14 were increased; while the tissue inhibitor metalloproteinase-2 (TIMP-2), and reversion-inducing cysteine-rich protein with kazal motifs (RECK) were both decreased. Furthermore, D. fortunei activated the gene and protein expressions of VEGF-A, -B and VEGFR-2, -3. Conclusions: D. fortunei increased MMP-2 activity, thereby stimulating angiogenesis and cell migration, both in vivo and in vitro, as a result of MMP-2 and TIMP-2 balance modulation and the activation of VEGF/VEGFRs expression.